2006
DOI: 10.1177/1078087405283794
|View full text |Cite
|
Sign up to set email alerts
|

Do Living Wage Policies Diffuse?

Abstract: This research note examines the conditions under which large U.S. cities pass living wage laws. It updates the only published article on the subject with new data and improved analytic methods. First, it shows that poverty, privatization, and the density of community organizations are associated with policy passage. Second, it provides new quantitative evidence that the living wage movement is, in part, a diffusion process associated with national community-organizing networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 16 publications
4
20
1
Order By: Relevance
“…Median income and unemployment thus control for general economic well‐being and job market characteristics. While studies of congressional voting found no relationship between economic indicators and roll call votes (e.g., Krehbiel & Rivers, ), at least one Canadian study found unemployment to be related inversely to wage rates (Blais, Cousineau, & McRoberts, ) and successful living wage ordinances are found in cities with higher poverty rates (Martin, ). While the null results are consistent with the general tenor of the early effects literature, recent research indicates the effects of wage increases are more variable and may be related to intrastate conditions.…”
Section: Model Specification Data and Methodsmentioning
confidence: 99%
“…Median income and unemployment thus control for general economic well‐being and job market characteristics. While studies of congressional voting found no relationship between economic indicators and roll call votes (e.g., Krehbiel & Rivers, ), at least one Canadian study found unemployment to be related inversely to wage rates (Blais, Cousineau, & McRoberts, ) and successful living wage ordinances are found in cities with higher poverty rates (Martin, ). While the null results are consistent with the general tenor of the early effects literature, recent research indicates the effects of wage increases are more variable and may be related to intrastate conditions.…”
Section: Model Specification Data and Methodsmentioning
confidence: 99%
“…A third theme of this topic concerns the antecedents and intervening variables that influence the adoption and success of living wage policies. Some scholars have considered the antecedent factors that determine whether or not an organization chooses to adopt a living wage policy (e.g., Martin, 2001Martin, , 2006Swarts & Vasi, 2011). For example, research on living wage organizations reveals the influence of trade unions (Prowse & Fells, 2016), and of leaders' social justice awareness and personal beliefs as key drivers for living wage adoption, and identifying longer-term challenges regarding organizational pay structures, strategy, and brand positioning (Werner & Lim, 2017).…”
Section: Contextual Variables Impacting Uptake and Success Of Living mentioning
confidence: 99%
“…Large, liberal cities located outside of the South are most likely to enact “living wage” policies, such as the $15 wage adopted in Seattle, San Francisco, and elsewhere (Swarts and Vasi 2011). High density of community organizations and a history of progressive activism are associated with the adoption of living wages (Lester 2014; Martin 2006). Proximity to other living wage cities matters (Martin 2006; Gallet 2004), as does access to direct democracy (Luce 2004; Lester 2014).…”
Section: State Minimum Wage Policy: Stepping Into the Voidmentioning
confidence: 99%
“…High density of community organizations and a history of progressive activism are associated with the adoption of living wages (Lester 2014; Martin 2006). Proximity to other living wage cities matters (Martin 2006; Gallet 2004), as does access to direct democracy (Luce 2004; Lester 2014). None of these studies examines the connection between federal and local action.…”
Section: State Minimum Wage Policy: Stepping Into the Voidmentioning
confidence: 99%